Ocena ryzyka wystąpienia urazów u czynnych zawodowo fizjoterapeutów z wykorzystaniem testu Functional Movement Screen (FMS) = Assessment of the risk of injury from professionally active physiotherapists using the Functional Movement Screen test (FMS) - Kochański, Bartosz; Kałużny, Krystian; Kałużna, Anna; Cichosz, Michał; Zukow, Walery; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2016)
Kochański Bartosz, Kałużny Krystian, Kałużna Anna, Cichosz Michał, Zukow Walery, Hagner-Derengowska Magdalena. Ocena ryzyka wystąpienia urazów u czynnych zawodowo fizjoterapeutów z wykorzystaniem testu Functional Movement Screen (FMS) = Assessment of the risk of injury from professionally active physiotherapists using the Functional Movement Screen test (FMS). Journal of Education, Health and Sport. 2016;6(7):479-487. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58635 http://ojs.ukw.edu.pl/index.php/johs/article/view/3711 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 25.07.2016. Ocena ryzyka wystąpienia urazów u czynnych zawodowo fizjoterapeutów z wykorzystaniem testu Functional Movement Screen (FMS) Assessment of the risk of injury from professionally active physiotherapists using the Functional Movement Screen test (FMS) Bartosz Kochański1, Krystian Kałużny1, Anna Kałużna1, Michał Cichosz2, Walery Zukow3, Magdalena Hagner-Derengowska1,4 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2 Jolly Med Szpital rehabilitacyjny Popielówek. Oddział rehabilitacji ogólnoustrojowej; 3 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy; 4 Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; Streszczenie. Wstęp. Specyfika pracy fizjoterapeuty związana jest z występowaniem obciążeń statycznych i dynamicznych narządu ruchu, które wpływają na zwiększenie ryzyka występowania urazów. Cel pracy. Celem pracy jest ocena ryzyka wystąpienia urazów u fizjoterapeutów na podstawie analizy podstawowych wzorców ruchowych według koncepcji Functional Movement System (FMS). Materiał i metody. Badania przeprowadzono na grupie 51 czynnych zawodowo fizjoterapeutów w tym 30 kobiet i 21 mężczyzn. Badania zostały przeprowadzone z wykorzystaniem urządzenia oraz protokołu do testu FMS. Dodatkowo każdy z uczestników badania wypełnił ankietę. Wyniki. Średni wynik w teście FMS u czynnych zawodowo fizjoterapeutów wynosi 13,51/21 pkt. Wykazano istotne statystyczne korelacje pomiędzy wynikiem testu FMS, a BMI, stażem pracy oraz wiekiem badanych. Nie wykazano korelacji pomiędzy wynikiem testu FMS, a płcią, przebytymi urazami i kontuzjami oraz aktywnością fizyczną. Wnioski. 1. U czynnych zawodowo fizjoterapeutów obserwuje się nieprawidłowości w podstawowych wzorcach ruchowych w teście FMS. 2. Ryzyko wystąpienia urazu u fizjoterapeutów wg testu FMS jest duże. Test FMS – 13,51/21. 3. Im większy wskaźnik BMI, staż pracy oraz wiek, tym większe ryzyko wystąpienia urazu u fizjoterapeutów wg testu FMS. Abstract Introduction. Specificity of physiotherapists work is associated with the occurrence of static and dynamic overload of locomotor system, that lead to more risk of injuries. Aim of the study. The aim of the study is to assess the risk of injury in physiotherapists on the basis of the analysis of the fundamental movement patterns according to the concept Functional Movement System (FMS). Material and Methods. The study was conducted on a group of 51 professionally active physiotherapists including 30 women and 21 men. The tests were conducted using the device and protocol of FMS test. Additionally, each of the study participants completed a questionnaire. Results. The average score in the FMS test in professionally active physiotherapists was 13.51/21 points. It has been shown statistically significant correlations between FMS test result, and BMI, duration of employment and the age of the respondents. There was no correlation between the test result FMS, and gender, a history trauma and injuries and physical activity. Conclusions. 1. In professionally active physiotherapists observed irregularities in the basic movement patterns in the test FMS. 2. Risk of injury in physiotherapists by FMS test is high. Test FMS - 13.51/21. 3. The higher BMI, duration of employment and age, the higher the risk of injury in physiotherapists by FMS test. Słowa kluczowe: Functional Movement Screen (FMS), fizjoterapeuci, urazy. Keywords: Functional Movement Screen (FMS), physiotherapists, injuries.